549 Characterizing double positive T cells in the tumor microenvironment: a tale of promiscuous cell fates. (9th November 2020) - Schad, Sara; Chow, Andrew; Pan, Heng; Mangarin, Levi; Zappasodi, Roberta; Gigoux, Mathieu; Redmond, David; Hirschhorn-Cymerman, Daniel; Budhu, Sadna; Zhong, Hong; Yang, Xia; Elemento, Olivier; et al.
Abstract : Background: CD4 and CD8 T cells are genetically and functionally distinct cell subsets of the adaptive immune system that play pivotal roles in immune surveillance and disease control. During development in the thymus, transcription factors ThPOK and Runx3 regulate the differentiation and maturation of these two lineages into single positive T cells that enter the periphery with mutually exclusive expression of either the CD4 or CD8 co-receptor. 1–2 Despite our expectation that these two cell fates are fixed, mature CD4+CD8+ double positive (DP) T cells have been described in the context of numerous immunological responses, including cancer, but their molecular and functional properties and therapeutic relevance remain controversial and largely unknown. 3–5 Methods: Our lab has identified and characterized a heterogenous DP T cell population in murine and human melanoma tumors comprised of CD4 and CD8 T cells re-expressing the opposite co-receptor and a parallel uptake in the opposite cell type's phenotype and function. Using CD4 (Trp1) and CD8 (Pmel) transgenic TCR T cells specific to B16 melanoma antigens gp75 and gp100 respectively, we demonstrate the re-expression of the opposite co-receptor following adoptive T cell transfer in B16 melanoma tumor bearing mice. Results: Specifically, up to 50% of transferred CD4 Trp1 T cells will re-express CD8 to become a DP T cell in the tumor microenvironment. Further, these CD4 derived DP T cells upregulate CD8 lineage regulator Runx3 and cytolytic genes Gzmb, Gzmk, and Prf1 to become potent cytotoxic T cells. Alternatively, a subset of CD8 Pmel T cells differentiate into DP T cells characterized by the increased expression of CD4, ThPOK, and regulatory marker FoxP3 (figure 1). In addition, we utilized 10x single cell and ATAC sequencing to further characterize these divergent DP T cell populations among open repertoire T cells isolated from murine and human melanoma tumors. Conclusions: Our findings highlight the capability of single positive T cells to differentiate in response to antigen and local stimuli into novel T cell subsets with polyfunctional characteristics. The resulting cell subsets will potentially affect the tumor microenvironment in distinct ways. Our studies may inform therapeutic approaches to identify antigen specific T cells as well as innovative signaling pathways to target when genetically engineering T cells to optimize cytotoxic function in the setting of adoptive cell therapy. Ethics Approval: The human biospecimen analyses were approved by Memorial Sloan Kettering Cancer Center IRB #06-107 References: Ellmeier W, Haust L & Tschismarov R. Transcriptional control of CD4 and CD8 coreceptor expression during T cell development. Cell Mol Life Sci 2013;70:4537–4553. Luckey MA, et al. The transcription factor ThPOK suppresses Runx3 and imposes CD4+ lineage fate by inducing the SOCS suppressors of cytokine signaling. Nature Immunology 2014; 15, 638–645. Bohner P, et al. Double positive CD4(+)CD8(+) T Cells are enriched in urological cancers and favor T Helper-2 polarization. Front Immunol 2019; 10, 622. Nascimbeni M, Shin E-C, Chiriboga L, Kleiner DE & Rehermann B. Peripheral CD4(+)CD8(+) T cells are differentiated effector memory cells with antiviral functions. Blood 2004;104:478–486. Nishida K, et al. Clinical importance of the expression of CD4+CD8+ T cells in renal cell carcinoma. Int Immunol 2020;32:347–357.